2016
DOI: 10.1111/jdv.13578
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C may enhance key amplifiers of psoriasis

Abstract: These findings suggest that HCV infection upregulates these inflammatory cytokines, possibly increasing susceptibility to developing psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 48 publications
0
35
0
2
Order By: Relevance
“…Moreover, HCV positive ratio in patients with psoriasis showed an increasing quadratic curve with age, implying that HCV infection affected de novo onset of psoriasis, especially late-onset psoriasis in HCV positive patients [ 84 ]. The possible role of HCV infection in developing psoriasis has been studied by Chun et al [ 85 ]. They found that the psoriatic skin of HCV-positive patients showed increased mRNA expression levels of cathelicidin, toll-like receptor 9, and IFNγ than that psoriatic skin of HCV-negative patients, suggesting that activation of inflammatory cytokines in HCV infected patients could enhance their susceptibility to psoriasis [ 85 ].…”
Section: The Risk Of Infection In Psoriasis and Psoriatic Arthritimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HCV positive ratio in patients with psoriasis showed an increasing quadratic curve with age, implying that HCV infection affected de novo onset of psoriasis, especially late-onset psoriasis in HCV positive patients [ 84 ]. The possible role of HCV infection in developing psoriasis has been studied by Chun et al [ 85 ]. They found that the psoriatic skin of HCV-positive patients showed increased mRNA expression levels of cathelicidin, toll-like receptor 9, and IFNγ than that psoriatic skin of HCV-negative patients, suggesting that activation of inflammatory cytokines in HCV infected patients could enhance their susceptibility to psoriasis [ 85 ].…”
Section: The Risk Of Infection In Psoriasis and Psoriatic Arthritimentioning
confidence: 99%
“…The possible role of HCV infection in developing psoriasis has been studied by Chun et al [ 85 ]. They found that the psoriatic skin of HCV-positive patients showed increased mRNA expression levels of cathelicidin, toll-like receptor 9, and IFNγ than that psoriatic skin of HCV-negative patients, suggesting that activation of inflammatory cytokines in HCV infected patients could enhance their susceptibility to psoriasis [ 85 ].…”
Section: The Risk Of Infection In Psoriasis and Psoriatic Arthritimentioning
confidence: 99%
“…TNF‐α represents a key cytokine for both hepatitis C progression and psoriasis. Chun et al hypothesized that HCV infection may also increase expression of cathelicidin, IFN‐γ, and TLR9, thus further contributing to the pathogenesis of psoriasis, regardless of IFN treatment (Chun et al, ). TNF‐α inhibitors seem to be a safe and effective option in HCV positive psoriatic patients, but concerns exist about long‐term safety, impact on liver fibrosis progression and risk of immune‐mediated liver injury (Pompili, Biolato, Miele, & Grieco, ).…”
Section: Reported Cases Of Daas‐induced/exacerbated Psoriasismentioning
confidence: 99%
“…There is a well‐known epidemiological association between the two conditions, but there is little data on the pathogenic interaction . Recent research found upregulation of inflammatory cytokines in the skin of HCV patients with psoriasis . Furthermore, one previous study showed a correlation between psoriasis severity (PASI) and viral load …”
Section: Characteristics Of Clinical Casesmentioning
confidence: 99%